Ranking Universities - Halloin, Véronique (Éditions de l'Université de Bruxelles, 2009)
University rankings are 'hot'. Some universities, policy makers and journalists seem to take them quite seriously. At the same time, however, they are also fiercely criticized. The best known worldwide rankings tend, for instance, to have a strong anglo-saxon bias and tend to give insufficient valorisation to human sciences.